PENGEMBANGAN MULTIMEDIA INTERAKTIF UNGGAH-UNGGUH BASA JAWA (GAUNG BAJA) SEBAGAI MEDIA PEMBELAJARAN UNTUK KELAS IV SEKOLAH DASAR - Siska Septiani; Sripit Widiastuti; Adin Fauzi (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
Unggah-Ungguh Basa was one of the Javanese language materials taught at grade IV Elementary School. However, it was difficult for students to understand this material because the students were not interested in learning. Based on the existing problems, the purpose of this study was to produce suitable interactive multimedia as a learning media to attract the students’ interest in understanding “ unggah-ungguh basa” material. This research was research and development proposed by Sugiyono which was limited to five stages: (1) looking for potentials and problems, (2) collecting data, (3) designing products, (4) validating the design, (5) revising the product. This study was limited to the product revision stage after expert validation due to the constraints of the COVID-19 pandemic. The instrument used in this study was a questionnaire. The data were obtained and analyzed by using quantitative descriptive data analysis. According the material experts, the materials contained in the Interactive Multimedia Gaung Baja could be understood easily by the students with the percentage of 94.2% (very feasible). Furthermore, the score from the media experts was 91% (very feasible) because the Interactive Multimedia Gaung Baja contained an attractive appearance and several contents, such as materials, audios, videos, and quiz games to train students’ understanding. These results indicated that the Interactive Multimedia Gaung Baja was very feasible as a learning media for grade IV elementary school students.